Psychological processing of a kidney transplantation, perceived quality of life, and immunosuppressant medication adherence - Scheel, Jennifer Felicia; Schieber, Katharina; Reber, Sandra Therese; Jank, Sabine; Eckardt, Kai-Uwe; Grundmann, Franziska; Vitinius, Frank; De Zwaan, Martina; Bertram, Anna; Erim, Yesim (Patient Preference and Adherence, 2019)
Introduction: Though psychosocial well-being and quality of life generally improve after transplantation, a relevant proportion of patients suffers from psychosocial problems. Further analysis of the psychological coping after kidney transplantation is needed to identify patients at risk. The aim of this study was to examine the psychological response after kidney transplantation and its associations with health-related quality of life and immunosuppressant medication adherence.
CRIS-Team WoS Importer:2019-06-04